English about antivirus software - Syarif, Hisyam (International research journal of management, IT and social sciences, 2015)
Antivirus is a type of software used to detect existing viruses on the computer system. Antivirus software is also known as virus protection software. With this software, we can find out whether a computer system is exposed to a virus or not. In general, this software runs in the background or the background, and also perform a scan of all files that are accessed. In today's antivirus Progress has been transformed and has many uses associated with the virus. But also the computer's performance. The virus code also usually always updated by the antivirus developer. So the computer is ensured its empowering. Even by new viruses though.